Effect of mouthguard design on retention and potential issues arising with usability in sport. Issue 1 (8th November 2018) - Karaganeva, Raya; Pinner, Susan; Tomlinson, David; Burden, Adrian; Taylor, Rebecca; Yates, Julian; Winwood, Keith
Abstract: Background/Aims: Mouthguard retention could potentially increase an athlete's motivation to wear the device, due to potential improvements in physical comfort. The aim of this study was to examine the retentive properties of selected customised mouthguard designs, during normal conditions (dry) and within the presence of artificial saliva (wet). Additionally, the correlation between thickness and retention was investigated. Material and Methods: Six different custom mouthguard designs (MG1‐MG6) reported in previous studies, were pressure‐formed with 2 and 4 mm blanks accordingly. Thickness was measured 10 times at seven anatomical points and the mean (±SD) was recorded. A novel rig was fabricated to connect the mouthguards to a Hounsfield H10KS Tensometer, which was used to fully displace each device from the model at a constant rate of 50 mm/min. The test was repeated under both dry and wet conditions. Results: Retention forces recorded at the anterior region demonstrated higher measurements under wet conditions than dry ( P < 0.001). The total retention of the mouthguards was influenced by alterations in their design. Trend analysis indicated that 64% of MG retention could be explained by their thickness under dry conditions and 55% when wet. Conclusions: Design and thickness of mouthguards are key factors in retention. Mouthguard fabrication techniques should be considered in order to minimize dislodgment of the devices as well as potentially increasing the wearability of mouthguards during sport.